Targeted Delivery of RGD-CD146+CD271+ Human Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes Promotes Blood–Spinal Cord Barrier Repair after Spinal Cord Injury - Xie, Yong; Sun, Yi; Liu, Yudong; Zhao, Jinyun; Liu, Quanbo; Xu, Jiaqi; Qin, Yiming; He, Rundong; Yuan, Feifei; Wu, Tianding; Duan, Chunyue; Jiang, Liyuan; et al. (ACS nano, 2023)
Spinal cord injury (SCI) disrupts the blood–spinal cord barrier (BSCB), potentially exacerbating nerve damage and emphasizing the criticality of preserving the BSCB integrity during SCI treatment. This study explores an alternative therapeutic approach for SCI by identifying a subpopulation of exosomes with stable BSCB function and achieving a specific targeted delivery. Specific subpopulations of CD146+CD271+ umbilical cord mesenchymal stem cells (UCMSCs) were isolated, from which engineered exosomes (RGD-CD146+CD271+ UCMSC-Exos) with targeted neovascularization function were obtained through gene transfection. In vivo and in vitro experiments were performed to explore the targeting and therapeutic effects of RGD-CD146+CD271+ UCMSC-Exos and the potential mechanisms underlying BSCB stabilization and neural function recovery. The results demonstrated that RGD-CD146+CD271+ UCMSC-Exos exhibited physical and chemical properties similar to those of regular exosomes. Notably, following intranasal administration, RGD-CD146+CD271+ UCMSC-Exos exhibited enhanced aggregation at the SCI center and demonstrated the specific targeting of neovascular endothelial cells. In the SCI model, intranasal administration of RGD-CD146+CD271+ UCMSC-Exos reduced Evans blue dye leakage, increased tight junction protein expression, and improved neurological function recovery. In vitro testing revealed that RGD-CD146+CD271+ UCMSC-Exos treatment significantly reduced the permeability of bEnd.3 cells subjected to oxygen-glucose deprivation, thereby restoring the integrity of tight junctions. Moreover, further exploration of the molecular mechanism underlying BSCB stabilization by CD146+CD271+ UCMSC-Exos identified the crucial role of the miR-501-5p/MLCK axis in this process. In conclusion, targeted delivery of RGD-CD146+CD271+ UCMSC-Exos presents a promising and effective treatment option for SCI.